Kemampuan Guru Penggerak dalam Program Merdeka Belajar di Daerah Jember - Fitriyah, Chumi Zahroul; Wardani, Rizki Putri; Rofiq, Annur (Scholarly Journal of Elementary School, 2023)
Guru Penggerak is one of the independent learning programs that is expected to increase teacher competence with several programs and encourage learning independence for students. The purpose of this study is to identify the ability of Guru Penggerak in implementing independent learning classes. This type of research is a qualitative research with an interview, field survey, and observation approach. Data analysis using data reduction, data triangulation, and data synthesis. The results of the study show that teachers have sufficient professional competence in the ability of teachers to drive independent learning.